Effectiveness of Using Wayang Beber Kreasi on Children's Storytelling Ability - Misbah Arwani; Rifa Suci Wulandari; Saiful Anwar (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
This study was conducted to determine the effectiveness of the use of wayang beber creative media on the storytelling abilities of group B PAUD Merak Ponorogo students in 2020. The research design used is experimental research in the form of Quasi Experimental Design. Data collection techniques used in this study are observation and documentation. The research instrument used was observation and documentation guidelines. To test the research hypothesis, the data analysis technique used is t-test. Prior to the t-test, the prerequisite tests were tests for normality and homogeneity. Based on the data analysis test carried out with the help of SPSS 18, it showed a significance value (2-tailed) for the Equal Variances Assumed column of 0.001 0.05, then H0 was rejected and Ha was accepted. The results of testing the data indicate that the use of wayang beber creative media is effective on children's storytelling abilities.